Relativistic model for the nonmesonic weak decay of single-lambda hypernuclei - Fontoura, C. E. [UNESP]; Krmpotic, F. [UNESP]; Galeao, A. P. [UNESP]; De Conti, C. [UNESP]; Krein, G. [UNESP] (Iop Publishing Ltd, 2016)
Having in mind its future extension for theoretical investigations related to charmed nuclei, we develop a relativistic formalism for the nonmesonic weak decay (NMWD) of single-Lambda hypernuclei in the framework of the independent-particle shell model and with the dynamics represented by the (pi, K) one-meson-exchange model. Numerical results for the one-nucleon-induced transition rates of C-12(Lambda) are presented and compared with those obtained in the analogous nonrelativistic calculation. There is satisfactory agreement between the two approaches, and the only noteworthy difference is that the ratio Gamma(n)/Gamma(p) is appreciably higher and closer to the experimental value in the relativistic calculation. The ability of describing existing data, including the most recent ones, on NMWD of Lambda-hypernuclei, warrants application of the formalism to evaluate similar decay processes in charmed nuclei.
Keywords: relativistic nuclear models; strange hypernuclei; charm hypernuclei; nonmesonic weak decay